The Impact of 'Long COVID-19' Symptoms on Stroke Patients During The COVID-19 Pandemic - Wahyu Dwihardi Raputra (Magna Neurologica, 2023)
Background: Coronavirus disease 2019 (COVID-19) has become a global pandemic, affecting millions of people. However, the relationship between COVID-19 and acute cerebrovascular diseases is unclear. Objective: This study aims to examine the potential effect of long COVID-19 on stroke patients. Methods: A descriptive approach was employed in this study to effectively portray and elucidate the facts, data, and information that were gathered from literature studies, including books, journals, and, and results related to the topic. Results: The results showed that stroke sufferers experienced several impacts due to their long COVID conditions. These perceived effects ranged from seizures to cognitive impairment or brain fog, encephalitis, as well as other symptoms that are likely to aggravate the condition of stroke sufferers. Conclusion: The presence of the pandemic has introduced further obstacles for stroke patients who are also dealing with long COVID-19 conditions. If left unattended, these challenges can result in heightened complications, severity, comorbidities, and eve death. Therefore, the government needs to prioritize the prevention and control of long COVID condition among patients to minimize its impacts and effects.